Use of digital technologies in public health: a narrative review - Castiglia, Paolo; Dettori, Marco; Arghittu, Antonella; Campus, Guglielmo; De Vito, Danila (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Websites, social media networks and mobile applications constitute important communication tools, while simultaneously enabling the population to increase their knowledge of health issues. This study aims to describe digital health experiences in Public Health to examine the different possible uses of digital technologies by Public Health Operators (PHOs) and Health Care Workers (HCWs) and the role these tools play in the efficiency of the health interventions undertaken. Methods: A narrative literature survey was conducted by consulting the PubMed and Scopus databases to find articles relevant to the topic of interest. The selection criteria adopted for manuscript screening involved including the survey studies dealing with the use of digital means such as new media in Public Health, published between 1 January 2012 and 31 May 2021.Results: Based on the keywords, 2,019 manuscripts were identified, of which 45 were included. The articles were grouped according to the digital tool (social media network, mobile application and websites) employed by PHOs and/or HCWs in health promotion initiatives. Specifically, this was broken down into: i) the use of social media in public health: 24 articles, ii) the use of mobile applications: 10 articles, iii) the use of websites: 8 articles and iv) the use of the three digital tools combined: 3 articles.Conclusions: The results of this study indicate that digital technologies may play a useful role in Public Health to improve communication between health professionals and patients, provide quality care even remotely and facilitate the achievement of health outcomes for the population from a Health Literacy perspective.